Reconstruction of late Holocene vegetation and climate of Hluhluwe Mfolozi area using phytoliths - Gallaher, Kirsten S L (Department of Biological Sciences, 2017)
This study presents a phytolith record from a late Holocene sedimentary core from the Hluhluwe-iMfolozi area in northeastern KwaZulu-Natal. Radiocarbon dating showed the oldest sediments to be from 23 80 ± 40 BP. Phytoliths are present throughout the record. There was a high degree of unclassifiable phytoliths (>79% per sub-sample), but preliminary trends identified include a dominance of C₄ grasses throughout (Chloridoideae and Panicoideae; adapted to higher temperatures and greater insolation), and slightly more C₃ grasses (Pooideae; adapted to cooler temperatures and/or winter rainfall) towards the base. The tree cover density index (D/P) does not reflect increased bush encroachment at this site, but appears to show a closed forest at 36cm depth and relatively densely-wooded savannas throughout, while the humidity-aridity index (lph) and water stress index (Fs) suggest a move towards a xerophytic short grass savanna, and increased water stress at the top of the sequence, which could reflect the climate becoming hotter and drier due to global warming. Future studies should be done to identify phytoliths specific to the vegetation of the study site and to calibrate the indices used to confirm their utility for this area.